Five new species of genus Kisaura Ross (Trichoptera: Philopotamidae) from Himachal Pradesh (India) - Pandher, Manpreet Singh; Saini, Malkiat Singh (Zootaxa, 2015)
Five new species of Kisaura Ross are described and illustrated from the Indian Himalaya. Newly described species are Kisaura trailaensis sp. n., K. barotensis sp. n., K. monospinata sp. n., K. sachensis sp. n. and K. curvata sp. n. In addition, K. madhyamika Schmid is recorded from Himachal Pradesh and a catalogue of Indian species of Kisaura is provided.